Answer:
See Below
Explanation:
For each of these, you just replace x with what's in the parenthesis.
f(-2) = 4(-2)^2 - 2(-2) + 1
f(-2) = 16 + 4 + 1
f(-2) = 21
g(5) =
![√(4(5) - 16)](https://img.qammunity.org/2023/formulas/mathematics/college/l2xq4k2a2wa9qaek982es0xgm0tkilab9t.png)
g(5) =
![√(20-16)](https://img.qammunity.org/2023/formulas/mathematics/college/mk3zvczqwj728jnhozpaib7c14k69bug8l.png)
g(5) =
![√(4)](https://img.qammunity.org/2023/formulas/mathematics/middle-school/3x3pq2h202thpbntw5o5fsij8epdj42fps.png)
g(5) = 2
f(3r) = 4(3r)^2 - 2(3r) + 1
f(3r) = 4(9r^2) - 6r + 1
f(3r) = 36r^2 - 6r + 1
f(a+b) = 4(a+b)^2 - 2(a+b) +1
f(a+b) = 4 (a^2 + 2ab + b^2) - 2a - 2b + 1
f(a+b) = 4a^2 + 8ab + 4b^2 - 2a - 2b + 1